2014
DOI: 10.1364/oe.22.014688
|View full text |Cite
|
Sign up to set email alerts
|

Independently tunable double Fano resonances in asymmetric MIM waveguide structure

Abstract: In this paper, an asymmetric plasmonic structure composed of a MIM (metal-insulator-metal) waveguide and a rectangular cavity is reported, which can support double Fano resonances originating from two different mechanisms. One of Fano resonance originates from the interference between a horizontal and a vertical resonance in the rectangular cavity. And the other is induced by the asymmetry of the plasmonic structure. Just because the double Fano resonances originate from two different mechanisms, each Fano res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(73 citation statements)
references
References 27 publications
1
70
1
1
Order By: Relevance
“…The values of FOM is as high as ~3200 at λ=1145 nm, which is due to the sharp asymmetric Fano line shape with ultra-low transmittance at this wavelength. These FOM values are significantly greater than that in the previous reports [14], [39].…”
Section: Structures and Simulationscontrasting
confidence: 74%
“…The values of FOM is as high as ~3200 at λ=1145 nm, which is due to the sharp asymmetric Fano line shape with ultra-low transmittance at this wavelength. These FOM values are significantly greater than that in the previous reports [14], [39].…”
Section: Structures and Simulationscontrasting
confidence: 74%
“…It's worthy to notice that those values are obtained due to the approximation that the line shape of the optical response spectrum nearly maintains the same, only leading to a red-shift [13,14], and it's also been proved by the later analysis. Based on the definition of figure of merit [8] and the consideration that detection used in sensor, such as biosensor, usually by measuring the light intensity variation for one particular wavelength, here we give a precise analytical expression for FOM at frequency ω as…”
Section: Structure and Analytical Expressionmentioning
confidence: 65%
“…Lately, the nanoresonator-coupled metal-dielectric-metal (NCMDM) waveguide structure, with advantages of easy fabrication, light manipulation and convenient integration, has also been found available for the sensor research [13][14][15]. Lu et al reported a plasmonic sensor in a waveguide system and got a figure of merit (FOM) of ~500 [13], and Qi et al also observed a sensing phenomenon in the MDM waveguide structure and achieved FOMs over 650 [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, plasmon rulers [8], core-shell structures [9], plasmonic nanoparticle clusters [10], composite cut-wire structures [11], planar plasmonic structure [12], and other structures [13][14][15] have been investigated theoretically or experimentally to obtain Fano-like resonances. It is worth to point out that plasmonic metal-dielectric-metal (MDM) waveguide structures have also received a lot of interest in studying Fano resonance due to the advantages of high integration, deepsubwavelength confinement of light, and easily manufactured [16][17][18][19][20]. Sharp and asymmetric Fano-line shapes were found in an MDM waveguide with multiple output ports, which were isolated by the baffles [21].…”
Section: Introductionmentioning
confidence: 99%